Tidal forecasting using RNN in Bahia Blanca estuary, Argentina - Pierini, Jorge Omar (2009)
In  recent  years,  the  availability  of  accurate  ocean  tide models has  become  increasingly  important,  as  tides  are  the  main  contributor  to disposal and movement of  sediments,  tracers and pollutants,  and  also  due  to  a  wide  range  of  offshore  applications  in  engineering,  environmental  observations,  exploration  and  oceanography. Tides  can be  conventionally predicted by harmonic  analysis,  which  is  the  superposition  of  many  sinusoidal  constituents  with  amplitudes  and  frequencies  determined  by  a  local analysis  of  the  measured  tide.  However,  accurate  predictions  of tide  levels  could  not  be  obtained without  a  large  number  of  tide  measurements  by  the  harmonic  method.  An  application  of  the  back-propagation  artifcial  neural  network  using  long-term  and  short-term  measuring  data  is  presented  in  this  paper.  On  site  tidal  level  data  at  Ingeniero  White  harbor  in  the  inner  part  of  Bahia Blanca  estuary, Argentina, will  be  used  to  test  the  performance  of  the  present model. Comparison with  conventional  harmonic  methods  indicates  that  the  back-propagation  neural  network model also predicts accurately  the  long-term  tidal  levels.